(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
Starting a teaching career is always problematic for many teachers because of the discrepancies that exist between theory and practice. Novice teachers usually encounter many difficulties when they try to make use of the theoretical background they acquired during their educational phase at the university. They are often faced by many challenges that require a certain training that is unfortunately missing from their curriculum. The present research paper aims at confirming the discrepancy hypothesis and exploring ways of bridging the gap between teachers’ training and classroom practices in the Algerian Middle schools so as to equip teachers with the necessary didactic tools to carry out their mission in the most favourable conditions. To reach our aim, we interviewed two inspectors in charge of the eastern region. The findings revealed the mismatch between theory and practice, besides we came up with the conclusion that a successful teaching can only be achieved through the integration of practical courses and pre-servicetraining in order to bridge the gap between what is theoretically taught to future teachers and the requirements of the actual classroom practices. Keywords - teachers’, training, classroom practices, EFL, curricula